2007
DOI: 10.2108/zsj.24.855
|View full text |Cite
|
Sign up to set email alerts
|

Righty Fish Are Hooked on the Right Side of Their Mouths – Observations from an Angling Experiment with Largemouth Bass, Micropterus salmoides

Abstract: The development of muscles and bones in fish is laterally asymmetric (laterality). A "lefty" individual has a "C"-shaped body, with its left-side muscles more developed and the left side of its head facing forward. The body of a "righty" is the mirror-image. This laterality causes asymmetric interactions between individuals of different fish species, in that a righty or lefty fish consumes more lefty or righty fish, respectively. To investigate the coupling mechanisms between body asymmetry and predatory behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 13 publications
3
35
0
1
Order By: Relevance
“…In another marked contrast to primary asymmetry, secondary asymmetry has frequently evolved from symmetry as well as through polarity reversal (Palmer, 2004). Thus, the polarity of the secondary asymmetry is far more variable among species, as in bivalve shells (Odhner, 1919) and flounder eyes (Policansky, 1982), and within species, as in crab claw (Shigemiya, 2003) and fish body shape (Nakajima et al, 2007).…”
Section: Evolution Of Lr Reversal In the Secondary Asymmetry Of Snailsmentioning
confidence: 99%
“…In another marked contrast to primary asymmetry, secondary asymmetry has frequently evolved from symmetry as well as through polarity reversal (Palmer, 2004). Thus, the polarity of the secondary asymmetry is far more variable among species, as in bivalve shells (Odhner, 1919) and flounder eyes (Policansky, 1982), and within species, as in crab claw (Shigemiya, 2003) and fish body shape (Nakajima et al, 2007).…”
Section: Evolution Of Lr Reversal In the Secondary Asymmetry Of Snailsmentioning
confidence: 99%
“…(Ministry of the Environment, Government of Japan, 2004). Morphological antisymmetry occurs in both species (Seki et al, 2000;Nakajima et al, 2007;Yasugi and Hori, 2011), and the predominance of cross-predation has been demonstrated in their predator-prey interaction . Accordingly, we carried out a behavioral test of predation events using these two species, and investigated the interactions between the predatory behavior of bass and the evasive response of goby with respect to their dimorphism.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies in some fishes have demonstrated that the leftward or rightward bias in the behavioral direction of each individual corresponds to morphological asymmetry, specifically antisymmetry (Hori, 1993;Nakajima et al, 2007;Takeuchi et al, 2010;Hata et al, 2011). This antisymmetry is defined as a dimorphism in which one side of the body is structurally and/or functionally more developed than the other side, and is distinguished from fluctuating or directional asymmetry (Palmer and Strobeck, 1986;Palmer, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations